Answer:
B
Step-by-step explanation:
Answer:
x = -9/5
y = 16/5
Step-by-step explanation:
-3x-2y=-1 first you need to multiply the numerator by 3 so when adding
4x+6y=12 the y's cancel and you get a single variable
3(-3x-2y=-1) —> -9x - 6y = -3 then you add the like terms
4x+6y=12 —> 4x + 6y = 12
(-9x+4x) + (6y - 6y) = (-3 + 12)
-5x = 9 then you divide by -5
x = -9/5
then you plug this in to either equation
4(-9/5) + 6y = 12
-36/5 + 6y = 12 then you add 36/5 to both sides
6y = 96/5 then you divide by 6
y = 16/5
Answer: D
Explanation:
Since we don't know the y-value of the vertex, let's do this an easy way: plugging in.
Let's use the y intercept since that would be the easiest. Since x=0, the terms with x cancel, and you will get a leading result of -5
A) results in 2, so eliminate it
B) results in -2, so eliminate it
C) results in 5, so eliminate it
D) results in -5, so keep it
Since D was the only one that worked, that is our correct answer.
Answer: The answer is -3 1/2 - 1/5
so it's C.
Step-by-step explanation: